UNJUK KERJA SOLARCOOKER TYPE PARABOLIC DENGAN DIAMETER 100 CM TINGGI 50 CM - JHON SUFRIADI PURBA (JURNAL ILMIAH MAKSITEK, 2020)
Has been done research on "The work of Solar cooker Type Parabolic with diameter 100 cm height 50 cm" This researchaims to know the performance of a Solar cooker with the experimental method of dish collector put in place exposed to directsunlight with water mass in containers 1 liter in 3 days observation. Observations were carried out with an interval of 10minutes from 10.00 WIB to 16.00 WIB. The research results for the 1liter mass reaches the highest temperature of 106 0C atthe average radiation intensity of the sun 492 W/m2. Besarya solar radiation intensity affects the thermal conversion systemto the focus field of the pan as a cooking container, the higher the radiation intensity then the higher the temperature of thepot cooker.